Prolactin gene polymorphism (−1149 G/T) is associated with hyperprolactinemia in patients with schizophrenia treated with antipsychotics - Ivanova, Svetlana A.; Osmanova, Diana Z.; Boiko, Anastasia S.; Pozhidaev, Ivan V.; Freidin, Maxim B.; Fedorenko, Olga Yu; Semke, Arkadiy V.; Bokhan, Nikolay A.; Kornetova, Elena G.; Rakhmazova, Lubov D.; Wilffert, Bob; Loonen, Anton J.M. (Schizophrenia research, 2017)
Antipsychotic drugs can cause hyperprolactinemia. However, hyperprolactinemia was also observed in treatment-naive patients with a first schizophrenic episode. This phenomenon might be related to the role of prolactin as a cytokine in autoimmune diseases. Extrapituitary prolactin production is regulated by an alternative promoter, which contains the functional single nucleotide polymorphism −1149 G/T (rs1341239). We examined whether this polymorphism was associated with hyperprolactinemia in patients with schizophrenia. We recruited 443 patients with schizophrenia and 126 healthy controls. The functional polymorphism −1149 G/T (rs1341239) in the prolactin gene was genotyped with multiplexed primer extension, combined with MALDI-TOF mass spectrometry. Genotype and allele frequencies were compared between groups with the χ2 test and logistic regression models adjusting for covariates. The frequency of genotypes and alleles in patients with schizophrenia did not differ from those in control subjects. A comparison between patients with schizophrenia with and without hyperprolactinemia revealed significantly higher frequency of the G allele in patients with hyperprolactinemia than in patients without it (χ2=7.25; p=0.007; OR=1.44 [1.10–1.89]). Accordingly, patients with hyperprolactinemia carried the GG genotype more frequently than patients without hyperprolactinemia (χ2=9.49; p=0.009). This association remained significant after adjusting the estimates for such covariates as sex, age, duration of the diseases and the dose of chlorpromazine equivalents. This study revealed a significant association between the polymorphic variant rs1341239 and the development of hyperprolactinemia in patients with schizophrenia. The serum prolactin concentration in patients with schizophrenia treated with antipsychotics may provide an indication of the activity of the gene that regulates extrapituitary prolactin production which is believed to play a role in the immune system.